A review of the genus Neoconger (Anguilliformes: Moringuidae), with the description of a new species - Smith, David G.; Marceniuk, Alexandre P.; Rotundo, Matheus M.; Carvalho, Cintia O.; Caires, Rodrigo A. (Zootaxa, 2024)
The genus Neoconger (family Moringuidae) is reviewed and our knowledge of it brought up to date. Six species are recognized, based on genetic and morphological information. Neoconger mucronatus Girard, 1858 occurs in the western Gulf of Mexico. Neoconger torrei (Howell Rivero, 1932) occurs in the Caribbean and along the coast of the Guianas. Neoconger anaelisae (Tommasi, 1960) occurs along the northern coast of Brazil. Neoconger hygomi n. sp. is described from a single specimen collected many years ago off Brazil’s southern coast. It is distinguished from the other species by the number of predorsal vertebrae (48 vs 32–45) and preanal vertebrae (55 vs 41–49). Neoconger vermiformis Gilbert, 1890 occurs in the eastern Pacific from the northern Gulf of California to Panama and northern Colombia. Neoconger tuberculatus (Castle, 1965) is known from two larvae collected off southeastern Australia. In addition, another species known only from larvae is reported from the Caribbean but is not named.